Multiple uncertainty, forward-futures markets and international trade - Jean-Marie Viaene; Itzhak Zilcha (Bank of Finland, 1995)
The optimum behavior of a competitive risk-averse international trader who supplies or demands commodities invoiced in foreign currency is examined when his profits are subject to several forms of risk: production, domestic cost, the exchange rate and the commodity price.The focus of the analysis lies in the optimality conditions for the level of trade and the extent of forward exchange and commodity futures commitments.New results on the implications of the framework for the separation and the double-hedging theorems are derived.The behavior of the same firm with and without complete markets is compared and conditions are obtained for a domestic price guarantee or a gradual introduction of missing markets to promote the level of international trade.
URN:NBN:fi:bof-20140807485
Keywords: D81; D84; F19; F31; 330